STRATEGI GURU DALAM KEGIATAN EKSTRAKURIKULER TILAWAH AL-QUR’AN MELALUI NAGHAM SISWA KELAS X DI SMAN 3 BAUBAU - Ainul, Ainul Yaqin Oktaviani; Sulasri; Rusli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies applied by teachers in Al-Qur'an tilawah extracurricular activities through nagham for tenth-grade students at SMAN 3 Baubau, as well as to identify the challenges faced and the efforts made by the teacher to address them. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana, and validated through source and technique triangulation. The findings reveal that the teacher applies six systematically integrated strategies, encompassing gradual nagham introduction starting from maqam Bayyati, step-by-step learning using short verses with one nagham per session, direct demonstration covering tonal variations and breathing techniques, nagham accuracy training through repeated and example-based correction, individual student ability mapping as the basis for personalized guidance, and independent practice assignments as learning extensions. The identified challenges include limited time allocation, low student self-confidence, technical difficulties in nagham mastery, heterogeneity in students prior reading abilities, and inconsistent independent practice. These challenges were addressed through material prioritization, a supportive learning atmosphere, personal mentoring, and motivational reinforcement. These findings contribute to the development of an adaptive nagham tilawah learning model in public schools, while also supporting the fourth SDGs goal on quality education through the cultivation of students religious character, self-confidence, and discipline.